E-business and telecommunications : 11th International Joint Conference, ICETE 2014, Vienna, Austria, August 28-30, 2014, Revised selected papers /: 11th International Joint Conference, ICETE 2014, Vienna, Austria, August 28-30, 2014, Revised selected papers. (2015) - Unknown
No abstract available